The Global Burden of Obstructive Sleep Apnea - Giannicola Iannella; Annalisa Pace; Mario Giuseppe Bellizzi; Giuseppe Magliulo; Antonio Greco; Armando De Virgilio; Enrica Croce; Federico Maria Gioacchini; Massimo Re; Andrea Costantino; Manuele Casale; Antonio Moffa; et al. (Diagnostics)
This study reviewed the global prevalence, health and socioeconomic impact, and management approaches of obstructive sleep apnea. The narrative review examined three key dimensions: (1) worldwide OSA prevalence across different regions, accounting for variations in diagnostic standards; (2) OSA’s effects on health outcomes and socioeconomic conditions across diverse populations and healthcare systems; and (3) current global approaches to OSA diagnosis, treatment, and public health management. Despite advances in diagnosis and treatment, a large proportion of OSA cases remain undiagnosed or inadequately managed. The findings show that untreated OSA significantly increases public safety risks, particularly regarding motor vehicle and occupational accidents, while also creating a substantial pool of patients at high risk for systemic complications with severe impacts on overall health. There is a critical need for increased public awareness, universal screening approaches, and integrated care strategies to address this global health challenge and reduce its considerable socioeconomic burden. Our review uniquely addresses global disparities in OSA prevalence, clarifies the health and socioeconomic impacts that remain underexplored in the current literature, and suggests concrete strategies for public health and clinical management improvement worldwide.